Using Reentry Simulations to Promote Changes in Attitude toward Offenders: Experiential Learning to Promote Successful Reentry - Moak, Stacy C. (American journal of criminal justice, 2020)
This research examines the viability of using reentry simulations as a tool for influencing changes in participants’ perspectives about the realities of coming back in the community after a period of incarceration. Using both quantitative and qualitative methodologies, we investigated changes in attitudes toward offenders after participants completed a reentry simulation designed to replicate the experience of the first four weeks in the life of a person attempting to reenter society after incarceration. Participants were 27 students enrolled in a community corrections course that was cross listed and co-taught between criminal justice and social work. Participants completed a quantitative pre- and post-test that assessed attitudes toward prisoners as well as a reflection assignment about the simulation experience. Wilcoxon Signed Rank Test was used to analyze scores from pre- and post-tests. Qualitative analysis of the reflection papers identified and analyzed themes. Both quantitative and qualitative analysis indicate that simulations humanize perspectives toward former offenders and develop a better understanding of their situation. This understanding creates empathetic feelings that can reduce discrimination and stigma, thereby creating an environment more conducive to successful reintegration. Based on the results of this study, use of simulation-based training is recommended with audiences including criminal justice personnel, service providers, court practitioners, judges, and legislators as a way to more clearly articulate the realities faced by this vulnerable population.